Organocatalytic Asymmetric Synthesis of Dihydroisoquinolinones via a One-Pot Aza-Henry–Hemiaminalization–Oxidation Sequence - Hahn, Robert; Jafari, Ehsan; Raabe, Gerhard; Enders, Dieter (Synthesis, 2015)
The asymmetric organocatalytic one-pot synthesis of trans-3,4-disubstituted 3,4-dihydroisoquinolin-1(2H)-ones is described. Starting from 2-(nitromethyl)benzaldehydes and various N-protected aldimines, 5 mol% of a quinine-based squaramide organocatalyst was used to synthesize the title compounds as virtually single diastereomers via an aza-Henry–hemiaminalization–oxidation sequence. Moderate to good yields (39–78%) and moderate to very good enantioselectivities (40–95% ee) were reached.
Keywords: organocatalysis; domino reaction; one-pot reaction; dihydroisoquinolinones; hydrogen bonding